Platinum anniversary: virus and lichen alga together more than 70 years - Petrzik, Karel; Vondrák, Jan; Kvíderová, Jana; Lukavský, Jaromír (PloS one, 2015)
Trebouxia aggregata (Archibald) Gärtner (phylum Chlorophyta, family Trebouxiaceae), a lichen symbiotic alga, has been identified as host of the well-known herbaceous plant virus Cauliflower mosaic virus (CaMV, family Caulimoviridae). The alga had been isolated from Xanthoria parietina more than 70 years ago and has been maintained in a collection since that time. The CaMV detected in this collection entry has now been completely sequenced. The virus from T. aggregata is mechanically transmissible to a herbaceous host and induces disease symptoms there. Its genome differs by 173 nt from the closest European CaMV-D/H isolate from cauliflower. No site under positive selection was found on the CaMV genome from T. aggregata. We therefore assume that the virus's presence in this alga was not sufficiently long to fix any specific changes in its genome. Apart from this symbiotic alga, CaMV capsid protein sequences were amplified from many other non-symbiotic algae species maintained in a collection (e.g., Oonephris obesa, Elliptochloris sp., Microthamnion kuetzingianum, Chlorella vulgaris, Pseudococcomyxa sp.). CaMV-free Chlorella vulgaris was treated with CaMV to establish virus infection. The virus was still detected there after five passages. The virus infection is morphologically symptomless on Chlorella algae and the photosynthesis activity is slightly decreased in comparison to CaMV-free alga culture. This is the first proof as to the natural presence of CaMV in algae and the first demonstration of algae being artificially infected with this virus.
Keywords: Molecular Sequence Data; Base Sequence; sekvence nukleotidů; Microscopy, Electron; elektronová mikroskopie; Anniversaries and Special Events; DNA virů; molekulární sekvence - údaje; Gold; výročí a významné události; zlato; sekvenční seřazení; Sequence Alignment; Caulimovirus; DNA, Viral; Chlorophyta